Determinação voltamétrica de ácidos orgânicos em sucos utilizando um eletrodo de pasta de carbono modificado com ftalocianina de cobalto (II) associado à calibração de segunda ordem - Silva, Amanda Cecília da (2019)
Low molecular weight organic acids such as citric, lactic, malic and tartaric are often used in the food and beverage industry because of their antioxidant and acidulant properties. For this reason, they are generally used to maintain the flavor of the beverages, regulate the pH, mask the unpleasant taste of some compounds, neutralize the sweet taste and/or acidify the taste. Therefore, the development of robust analytical methodologies, fast and with minimal waste generation for the monitoring of these acids in beverages is of great importance because they influence drastically the organoleptic properties, stability and microbiological characteristics of these products. This work demonstrates the electrocatalytic oxidation of citric, lactic, malic, succinic and tartaric acids in the cobalt (II)-phthalocyanine modified carbon paste electrode - CoPC-CPE for the development of a sensitive and direct method employing square wave voltammetry associated with multivias calibration techniques to circumvent interference problems found in the samples. Calibration models were constructed for each analyte by using partial least squares unfolded with residual bilinearization (U-PLS/RBL) and resolution of multivariate curves with alternating least squares (MCR-ALS). The models were evaluated by using the validation set (25 mixtures) obtained with the Taguchi design. A linear response range between 10 and 100 μmol L-1 was used to U-PLS/RBL and MCRALS models which presented REP range varying from 2.58% to 5.46% and 4.47% to 5.78%, respectively. Finally, the calibration models U-PLS/RBL and MCR-ALS were applied to nine samples of fruit juices. The results obtained in both models reached the second order advantage and demonstrated an excellent analytical performance. In addition, paired t-test was applying between the proposed and the reference methods (AOAC method 974.18) where it was possible to observe that there was no statistically significant difference at a confidence level of 95%. Therefore, the proposed method is an unprecedented alternative, simple, fast and with little residue generation for determination of organic acids in fruit juices.